Unveiling The Legacy of Siti Walidah (1872-1946): Exploring the Education, Life, And Works of Indonesian Female Ulama - Uyuni, Badrah; Adnan, Mohammad; Hamid, Abdul; Ma'arif, Samsul; Mahfuz, Mahfuz (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
This study delves into the da'wah contributions of the Indonesian female ulama, Siti Walidah (1872-1946). Employing qualitative methods, the research entails creating and observing various works, books, academic research, videos, internet sources, and historical documents. The gathered data undergoes analysis using the explanatory analysis method, where the logic of social phenomena aligns with common sense through historical, anthropological, and sociological approaches. The research aims to exemplify the role model provided by female ulama such as Siti Walidah, allowing contemporary women to learn from and emulate the activities and struggles of these female scholars, thereby yielding numerous benefits for the advancement of the ummah, particularly women. The study presents the concepts of women scholars, their contributions, and the strategies they employed. Additionally, it delves into the supporting and inhibiting factors faced by female ulama in their preaching endeavors, aiming for a comprehensive understanding of their experiences.